Compositionally tuned hybridization of n-type Ag0: Ag2Se under ambient conditions towards excellent thermoelectric properties at room temperature - Tee, Si Yin (2024)
It is important to tune the thermoelectric properties of n-type thermoelectric materials, orthorhombic Ag2Se by nanoscale hybridization apart from conventional alloying or ion-doping approaches. In this work, we report the thermoelectric performance of a series of n-type Ag0 : Ag2Se materials prepared through a surfactant-free, aqueous solution-based approach under ambient conditions. This strategy enables fine control over phases and compositions through nanoscale hybridization using silver nanoparticles for the first time, yet remains applicable to large-scale production methods. By prolonging reaction times, the synthetic process is carefully developed/optimized to adjust the excess of the Ag0 phase, in order to enhance the thermoelectric properties. Hybridization of Ag0 and Ag2Se with increasing amounts of Ag0 (1.96%, 4.31%, 6.10%, 15.97%, 45.80% and 50.86% Ag0) results in not only increased electrical conductivities but also decreased Seebeck coefficients. The optimal excess of Ag0 is determined to be 1.96% after 7 days of reaction, with a high ZT value of near unity at 333 K. The ZT values realized in this study exceed those hitherto reported for β-Ag2Se synthesized via wet chemistry methods at room temperature.